Experimental investigation of hub motors characteristics for tunnel inspection robots - Low, Wei Lun (2019)
A compact mobile robot has been designed and developed for sewer inspection in Deep Tunnel Sewerage System (DTSS) located in Singapore. Tunnel inspection robots requires motors that are able to provide sufficient torques at low speed to cope with various tunnel conditions from dry, muddy, to partially filled water. With advantages such as high torque capability, easy installation and waterproof ability, hub motors are chosen as the mechanical drive system of the tunnel inspection robot. Hub motor distributor is one of the problems encountered. With the hub motor supplier no longer available to supply them, outsourcing to another distributor is inevitable. However, it was found that every distributor has different motor performance for the same type of hub motor. The performance could also vary from different batches of production. Additionally, the distributors tend to either not give any information or provide inaccurate motor characteristics. To minimize the effect of this problem, it is essential to have in-house Quality Control of the motor. An experimental rig has been designed and developed using power train approach, where all elements are connected through the central axis of the shafts and power is transmitted through it. Before experiments are conducted, a review of existing hub motors is done to filter out those with lower torque capacity. The experiment is then carried out with 3 hub motors with high torque capacity. Through the experiments, the design of the experimental setup is proven to be feasible and the hub motor that is most suitable for the robotic platform is chosen based on the results. Conclusions and recommendations for future work are also included.